2017
DOI: 10.1007/s00737-017-0783-0
|View full text |Cite
|
Sign up to set email alerts
|

The association of exercise during pregnancy with trimester-specific and postpartum quality of life and depressive symptoms in a cohort of healthy pregnant women

Abstract: Few published studies have examined the relationship between exercise during pregnancy, quality of life (QOL), and postpartum depressive symptoms in healthy pregnant women. A prospective cohort of 578 healthy pregnant women were followed during their pregnancy through 6 months postpartum. Levels of self-reported exercise and QOL before, during, and following pregnancy were assessed using standardized questionnaires during each trimester of pregnancy and 6 months postpartum. Depressive symptoms were assessed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 53 publications
2
21
0
1
Order By: Relevance
“…It has also been shown that HRQoL might be compromised during pregnancy and that higher physical fitness plays a positive role in HRQoL . As the IFIS is a rather simple and quick‐to‐use tool that could be implemented in clinical practice, it is of clinical interest to investigate whether the IFIS can discriminate between both objectively measured physical fitness and HRQoL levels in pregnant women.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that HRQoL might be compromised during pregnancy and that higher physical fitness plays a positive role in HRQoL . As the IFIS is a rather simple and quick‐to‐use tool that could be implemented in clinical practice, it is of clinical interest to investigate whether the IFIS can discriminate between both objectively measured physical fitness and HRQoL levels in pregnant women.…”
Section: Introductionmentioning
confidence: 99%
“…12,31 Previous studies reported improved postpartum quality of life in women who exercised during pregnancy. 13,21 The results of the present study are suggestive of unsuitable ANE practices among these women. This may be evident from the prescribers of ANE, as reported by these women.…”
Section: Discussionmentioning
confidence: 53%
“…In some studies, ANE was related to improved postpartum QOL, wellbeing and reduction of postpartum depression, while in others there were no associations between ANE and postpartum health status. [17][18][19][20][21][22][23][24] In developing countries like Nigeria, empirical evidences are scarce on the impact of practice and/or patterns of ANE on postpartum health status of nursing mothers. There is need to evaluate the practice and patterns of ANE in mothers as well as how these antenatal health behaviours relate with postnatal health status.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it seems likely that pregnant women who receive more detailed advice regarding the benefits of exercising during pregnancy are more likely to perform a sufficient amount of exercise according to the ACOG guidelines (Santo et al, 2017). Indeed, healthy pregnant women who adhered to the ACOG guidelines for exercise exhibited significantly better physical and emotional health than those who did not follow these guidelines (Campolong et al, 2017). Moreover, the women who were taught to follow the ACOG guidelines when they exercised by their health care providers had a lower level of pregnancy-induced symptom distress.…”
Section: Discussionmentioning
confidence: 99%
“…According to guidelines issued by the American College of Obstetrics and Gynecology (ACOG), healthy pregnant women should engage in moderate-intensity exercise for at least 20-30 min/day on most days (ACOG, 2015). However, past studies have shown that women seldom adhere to the ACOG guidelines and tend to decrease the frequency and intensity of exercise to significantly less than the ACOG standards during pregnancy (Campolong et al, 2017;Lee, Chiang, Hwang, Chi, & Lin, 2016;Santo, Forbes, Oken, & Belfort, 2017;Tung, Lee, Lin, & Lin, 2014). This could be due to distress symptoms that arise with physiological changes, a fear of harming the fetus and, in turn, a reduced inclination to exercise (Campolong et al, 2017;Lee et al, 2016;Santo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%